Distinct clinical outcomes in pediatric tuberculosis: A study utilizing infant macaques exposed to aerosol Mycobacterium tuberculosis - Katherine Turnbull; Eunice Vincent; Huanbin Xu; Peter J. Didier; Robert V. Blair; Lara A. Doyle-Meyers; Chad J. Roy; Smriti Mehra; Deepak Kaushal; Ronald S. Veazey; Xiaolei Wang (iScience)
Summary: Clinically relevant pediatric animal models are required to advance research and therapies for Mycobacterium tuberculosis (Mtb) infections in children. Utilizing infant rhesus macaques exposed to controlled doses of aerosolized Mtb CDC1551, we systematically monitored physical changes and assessed signs of tuberculosis, including physical examinations, clinical blood chemistry, radiography, and histopathology. Our results demonstrated that infant macaques exposed a physiologically relevant, low dose of aerosolized Mtb CDC1551 and exhibited immune control of infection similar to that observed in human infants, while those exposed to a higher dose experienced widespread dissemination, rapid disease progression, and mortality within six weeks after Mtb exposure. These findings suggest that pediatric rhesus macaques exposed to a low dose of Mtb via the aerosol route could serve as a translational model for natural Mtb infection in children, thereby allowing for the recapitulation of the immunopathogenesis and treatment of pediatric tuberculosis in a clinical setting.